Peripheral Ulcerative Keratitis Associated with Granulomatosis with Polyangiitis Emerging Despite Cyclophosphamide, Successfully Treated with Rituximab - Fujita, Yuya (Intern Med, 2018)
A 67-year-old Japanese man was diagnosed with granulomatosis with polyangiitis based on the presence of right maxillary sinusitis, proteinase 3 antineutrophil cytoplasmic antibody positivity, and right scleritis. A conjunctival biopsy specimen showed neutrophil-predominant infiltration around the vessels without granuloma. Because there was a risk of blindness, pulsed methylprednisolone and intravenous cyclophosphamide pulse therapy (IVCY) were started. However, it was ineffective, and peripheral ulcerative keratitis newly emerged. We promptly switched the treatment from IVCY to rituximab, and ophthalmologists performed amniotic membrane transplantation, which avoided blindness. The close and effective working relationship between physicians and ophthalmologists improved our patient's ocular prognosis.